Formulasi dan Karakterisasi Tepung Komposit Berbahan Lokal Kaya Gizi untuk Diversifikasi Pangan dan Pencegahan Stunting: The Formulation and Characterization of Nutrient-Dense Composite Flour from Local Ingredients to Support Food Diversification and Stunting Prevention - Alfan Ridha; Titik Dwi Noviati; Mohammad Zainul Ma’arif; Nandine Hanifa Fatihah (Jurnal Ilmiah Pangan Halal, 2025)
Stunting remains a major chronic nutritional problem in Indonesia, affecting growth, cognitive development, and long-term productivity. One of the preventive efforts is the innovation of nutrient-dense local food products. This study aimed to develop composite flour based on soybean (Glycine max L.), white sweet potato (Ipomoea batatas L.), and carrot (Daucus carota subsp. sativus) as an alternative food ingredient to support food diversification and stunting prevention. A true experimental design with five replications was used, including the analysis of protein, ash, and moisture contents, as well as physical observations compared with wheat flour as a control. The results showed that the composite flour had higher protein content (11.68 ± 0.23 vs. 4.08 ± 0.11), higher ash content (4.73 ± 0.11 vs. 4.13 ± 0.46), and lower moisture content (0.64 ± 0.02 vs. 11.8 ± 0.41) than wheat flour (p < 0.001). Physically, the composite flour appeared cream-yellow due to β-carotene pigments from carrots, with a normal odor and powdery texture that met the Indonesian National Standard (SNI 3751:2009). This composite flour shows potential as a nutrient-dense, locally sourced food ingredient that supports food diversification, accelerates stunting reduction, and contributes to the development of high-quality, competitive halal food products.